The importance of morphological identification of African anopheline mosquitoes (Diptera: Culicidae) for malaria control programmes - Erica Erlank; Lizette L. Koekemoer; Maureen Coetzee (Malaria Journal, 2018)
Abstract Background The correct identification of disease vectors is the first step towards implementing an effective control programme. Traditionally, for malaria control, this was based on the morphological differences observed in the adults and larvae between different mosquito species. However, the discovery of species complexes meant that genetic tools were needed to separate the sibling species and today there are standard molecular techniques that are used to identify the two major malaria vector groups of mosquitoes. On the assumption that species-diagnostic DNA polymerase chain reaction (PCR) assays are highly species-specific, experiments were conducted to investigate what would happen if non-vector species were randomly included in the molecular assays. Methods Morphological keys for the Afrotropical Anophelinae were used to provide the a priori identifications. All mosquito specimens were then subjected to the standard PCR assays for members of the Anopheles gambiae complex and Anopheles funestus group. Results One hundred and fifty mosquitoes belonging to 11 morphological species were processed. Three species (Anopheles pretoriensis, Anopheles rufipes and Anopheles rhodesiensis) amplified members of the An. funestus group and four species (An. pretoriensis, An. rufipes, Anopheles listeri and Anopheles squamosus) amplified members of the An. gambiae complex. Conclusions Morphological identification of mosquitoes prior to PCR assays not only saves time and money in the laboratory, but also ensures that data received by malaria vector control programmes are useful for targeting the major vectors.